Effects Of Combination Of Vermicompos and Cow Urine Solution On Hydroganic Growth Of Melon (Cucumis Melo L.) - agus supriyanto (AGRONISMA, 2022)
Hydrogenic cultivation of melons is an alternative to using a narrow area of land, and utilizing organic waste from markets and farms into vermikomos fertilizer and liquid organic fertilizer can be a solution to reduce waste while at the same time being a source of nutrition for melon plants that are cultivated hydrogically. This study aims to determine the optimal dose of vermicompost fertilizer and cow urine solution on the growth, yield, and quality of melon plants. The experiment was conducted using a factorial randomized block design (RBD) with control using 2 factors,  factor 1 is the dose of vermicompost which consists of 5 levels: 200, 800, 1200, 1600 and 2000 g/polybag, factor 2 is the concentration of cow urine solution with a concentration of 10% and 20%/liter. Parameters observed were plant length, number of leaves, leaf area, fruit weight, fruit diameter, fruit flesh thickness, total dissolved solids. The results showed that V2C1 treatment (vermicompost dose of 800 g/polybag and 10% cow urine organic fertilizer concentration) gave an average plant length of 142.56 cm and number of leaves, with an average of 17.33 strands.